Par-delà les brumes du Nord : remarques sur la caractérologie juridique dans l’Historia om de nordiska folken d’Olaus Magnus (1555) - Gilduin Davy (Clio@Themis)
Olaus Magnus – like his brother Johannes – can be considered as a father of Gothicism as a movement of ideas generating a new anthropological approach of the North. Its Historia om de nordiska folken indeed initiates a new perception of the Scandinavian peoples (mainly Swedes) in which are exposed several primary values that configure a common political and legal identity. In any case, his description of the customs and characters of the ancient Nordics, based on the springs of Humanism (rediscovery of the theory of climates, new approach of otherness and barbarism in particular), participates to their integration into the vast European œkoumene and, notwithstanding the advances of the Reformation, prefigures the ideological projections that Montesquieu, Mallet, Herder and many others will sketch two centuries later.